Role of ocular cytology in vernal keratoconjunctivitis. Issue 1 (5th December 2019) - Bruschi, Gaia; Ghiglioni, Daniele G.; Osnaghi, Silvia; Rosazza, Chiara; Pires Marafon, Denise; Landi, Massimo; Marchisio, Paola G.
Abstract: Background: Children with vernal keratoconjunctivitis (VKC) present symptoms that are similar to other ocular allergies, but more pronounced, and are controlled using topical steroids. To avoid excessive and prolonged use of topical steroid eye drops, over the past 20 years galenic eye drops of cyclosporine with a concentration of 1% to 2% and tacrolimus with a concentration of 0.1% have been introduced as a treatment for the severe and unresponsive forms. The main symptoms of VKC occur most frequently during the spring and tend to get worse during the summer, meaning that affected children tend to avoid exposure to sunlight. The aim of this study was to assess the most common cell types present in the conjunctiva of children with VKC, how ocular treatment can influence them, and whether affected children express a typical conjunctival pattern, which could be useful as a pathognomonic pattern of VKC, allowing us to study this rare eye disease. Method: This was a cohort study of 56 children, of whom 17 were not receiving any treatment at the time of testing, 14 were using steroid eye drops or had taken them in the previous 10 days, and 25 were treated with cyclosporine eye drops or tacrolimus eye drops 0.1%. Result: Children in group 1 (no topical therapy) express more epithelial cells, neutrophils, mast cells, eosinophils, and lymphocytes than the other two groups. Conclusion: Given the ease of performance, when conducting further longitudinal studies, the conjunctival cytology examination could be used, on the one hand, to diagnose VKC, especially when the clinical diagnosis is uncertain, and, on the other, to follow disease evolution and monitor the response to topical treatment.